Pelatihan Pengelolaan Keuangan Keluarga Islami Bagi Ibu-Ibu PKK Kecamatan Ganding Kabupaten Sumenep - Khusnul Fikriyah; Lucky Rachmawati; Sri Abidah Suryaningsih; Clarashinta Canggih (Inspirasi Nusantara, 2021)
Family financial arrangements are needed to maintain the welfare of the family economy. For Muslim families, Islamic management is very much needed in order to maintain a balanced financial condition in the world and the hereafter. Community Service (PKM) is carried out in Ganding District, Sumenep Regency. In this area the majority of the population is Muslim, but their educational background is 78% of elementary school graduates, so it is estimated knowledge about Islamic financial management is still very low. The form of activities undertaken is training in Islamic family financial management. The purpose of this PKM is to introduce the community closer to the Islamic family financial management. It is hoped that this community service will be a solution for the community to be able to manage family finances in accordance with Islamic teachings, so that the income earned and used becomes more blessing. The results of the implementation of the PKM